2020
DOI: 10.1126/science.aaw8977
|View full text |Cite
|
Sign up to set email alerts
|

Diverse variola virus (smallpox) strains were widespread in northern Europe in the Viking Age

Abstract: Smallpox, one of the most devastating human diseases, killed between 300 million and 500 million people in the 20th century alone. We recovered viral sequences from 13 northern European individuals, including 11 dated to ~600–1050 CE, overlapping the Viking Age, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 126 publications
7
124
0
3
Order By: Relevance
“…Screening of a large sample of medieval remains indicated that smallpox was present in Europe by at least the 6 th century B.C.E.. However none of the strains isolated were closely related to modern strains ( Mühlemann et al, 2020 ). Instead a smallpox strain isolated from a seventeenth century Lithuanian mummy appears to be ancestral to all modern smallpox variants (of both variola major and variola minor) ( Duggan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Screening of a large sample of medieval remains indicated that smallpox was present in Europe by at least the 6 th century B.C.E.. However none of the strains isolated were closely related to modern strains ( Mühlemann et al, 2020 ). Instead a smallpox strain isolated from a seventeenth century Lithuanian mummy appears to be ancestral to all modern smallpox variants (of both variola major and variola minor) ( Duggan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, efforts were focused on detecting pathogenic species, tracking the development, spread, and prevalence of particular disease-causing microbes. Such efforts have resulted in new understandings of infectious disease, from the Black Death (Spyrou et al 2019) to Viking-era smallpox (Mühlemann et al 2020) to the colonial epidemics of the Americas (Vågene et al 2018). More recently, metagenomic analysis has yielded insights into ancient microbial communities, rather than a single taxon, from a range of substrates but particularly from human-associated microbial communities, such as the oral and gut microbiomes (Shillito et al 2020;Velsko and Warinner 2017).…”
Section: The Archaeology Of Fermentationmentioning
confidence: 99%
“…Authors note that the VARV O1L ortholog has been retained in all VARV isolates, therefore it is possible that the gene has undergone subsequent selection for optimal function in human cells and may be critical for dissemination and establishment of VARV within human hosts. When investigating the evolution of the VARV genome, investigators recently hypothesized genetic losses that have occurred during evolution of the virus [42]. Comparison of the genetic differences between modern VARV isolates compared to ancient isolates could identify potential genetic elements involved in the evolution of smallpox to becoming a solely human pathogen.…”
Section: Plos Pathogensmentioning
confidence: 99%